Demographic trends associated with substance use disorder and risk for adverse obstetric outcomes with cannabis and opioid use disorders. (30th December 2022) - Logue, Teresa C.; Wen, Timothy; Friedman, Alexander M.
Abstract: Background: Substance use disorders (SUDs) are increasing in the obstetric population, vary with demographic characteristics, and are associated with adverse pregnancy outcomes. Cannabis use disorder and opioid use disorder are two of the most common SUDs during pregnancy. Objective: This study had two objectives. The first objective was to assess trends in any SUD diagnosis during delivery hospitalizations from 2000 to 2018 by maternal age, ZIP code income quartile, and hospital location and teaching status. The second objective was to determine risk for adverse pregnancy outcomes during delivery hospitalizations specifically in the presence of cannabis and opioid use disorder diagnoses. Study design: We conducted a serial cross-sectional analysis of the 2000–2018 National Inpatient Sample. Delivery hospitalizations to women aged 15–54 years with substance use disorder diagnoses were identified. SUD included (i) cannabis use disorder; (ii) opioid use disorder; (iii) alcohol use disorder; and (iv) other drug use disorder. We used joinpoint regression to estimate the average annual percent change (AAPC) in any substance use disorder diagnoses with 95% confidence intervals (CIs) by (i) ZIP code income quartile, (ii) hospital location and teaching status, and (iii) maternal age. We used unadjusted and adjusted log-linear regression to evaluate the relationship between cannabis use disorder and opioid use disorder several adverse maternal outcomes. We report unadjusted and adjusted risk ratios (aRRs) as measures of effect. Results: From 2000 to 2018, trends analyses broadly demonstrated increasing risk for SUD across demographic categories. In trends analyses stratified by ZIP code-income quartile, the proportion of deliveries with any SUD diagnosis increased across each income quartile with significant increases in the lowest income quartile (AAPC 4.6%, 95% CI 0.4%, 8.9%), second lowest quartile (AAPC 6.3%, 95% CI 5.3%, 7.4%), second highest quartile (AAPC 5.4%, 95% CI 4.1%, 6.8%), and highest quartile (AAPC 4.4%, 95% CI 2.1%, 6.8%). A larger increasing AAPC for SUD was present for deliveries in rural hospitals (AAPC 12.3%, 95% CI 9.8%, 14.9%) as compared to teaching (AAPC 5.7%, 95% CI 5.2%, 6.3%) and non-teaching urban hospitals (AAPC 7.0%, 95% CI 5.9%, 8.1%). By maternal age group, there was a significant larger AAPC for SUD for women aged 15–19 years (AAPC 8.5%, 95% CI 6.6%, 10.4%), 20–24 years (AAPC 9.0%, 95% CI 6.9%, 11.1%) and 25–29 years (AAPC 9.8%, 95% CI 9.1%, 10.6%) than women ≥30 years of age. Cannabis use disorder was associated with increased adjusted risk for preterm delivery (aRR 1.44, 95% CI 1.43, 1.45) and abruption and antepartum hemorrhage (aRR 1.77, 95% CI 1.75, 1.80). Opioid use disorder was associated with risk for non-transfusion severe maternal morbidity (aRR 1.73, 95% CI 1.67, 1.79), preterm delivery (aRR 1.75, 95% CI 1.74, 1.77), and abruption and antepartum hemorrhage (aRR 2.15, 95% CI 2.11, 2.19). Conclusion: While substance use disorders are increasing in pregnancy across rural and urban settings, age groups, and income quartiles, several populations are associated with higher increased risks and trends. These findings support that SUDs are likely to continue to be of public health significance in diverse geographic and demographic settings.